BRAKING OF HIGH-SPEED PASSENGER TRAINS WITH REGARD TO THE OPERATION OF AN ELECTROMAGNETIC RAIL BRAKE - Naumenko, N. Je.; Khyzha, I. Ju.; Boghomaz, Je. H. (Science and Transport Progress, 2009)
The research of the braking process of high-speed passenger train with the use of compressed-air, electropneumatic and electromagnetic track brakes is carried out. The dependences of braking distance on motion speed for vehicles equipped by block or disk brakes as well as for a case of electromagnetic track brakes used in addition to existing braking means.